Socioeconomic and Geographical Inequities in Burden and Treatment seeking Behavior for Hypertension among Women in the Reproductive Age (15–45 years) Group in India: Findings from a Nationally Representative Survey - Karthiga Vijayakumar; Sivaranjini Kannusamy; Yuvaraj Krishnamoorthy; Kavita Vasudevan; Pruthu Thekkur; Sonu Goel; Soumya Swaroop Meshram (Indian Journal of Public Health)
Background: Socioeconomic disparity changed healthcare seeking and management cascade of hypertension due to inequity in hypertension care cascade pathway. Objectives: The inequities in burden and treatment-seeking behavior of hypertension among reproductive age group women were studied from National Family Health Survey-4 (NFHS-4) data. Materials and Methods: We analyzed the data from NFHS-4 of women of reproductive age group between 15 and 49 years among the selected households contributing to 699,686 women. Socioeconomic inequities were assessed by expenditure quintile. Inequities in burden and treatment-seeking behavior were reported using the concentration curve and concentration index. Results: The prevalence of hypertension in India was 15% (95% confidence interval: 14.9%–15.4%). One-third (32%) of the hypertensive population received treatment and only 28% of the women had controlled blood pressure. Wealth and education-based inequalities were more in high wealth index. The inequity in screening and awareness was in the northern and northeastern regions. Conclusion: There was inequity in the overall hypertension care cascade pathway with more inequity in the northern and northeastern region.